Undergraduate Students’ Perspective On The Use Of Padlet As Learning Tool For English Writing - Silvia Nanda Putri Erito (JELLE : Journal Of English Literature, Linguistics, and Education, 2022)
The impact of post-covid-19 made lecturers think hard to keep using digital learning and developing the use of ICT in conducting learning activities. One of the digital learning tools used is Padlet. This study aims to explain students' perceptions of using Padlet, particularly in English writing class. A total of twenty-five students in the fourth-grade semester of the English department at the University of Muhammadiyah Semarang. The research design was a qualitative case study. The data was gathered through an open-ended questionnaire. The findings showed that the students perceived the use of Padlet as a learning English writing tool positively, they think Padlet help them to learn English writing and provides simple activities that encourage them to enjoy the learning process, and they perceived that Padlet enhances their motivation and create collaborative learning and student relationship. Theoretically, the use of Padlet in English writing could be implemented as a media tool to provide writing. Practically, the result of the research benefits EFL learners and practitioners. Pedagogically, the implementation of Padlet needed student-lecturer collaboration to achieve the objective of the learning. The researchers suggested that adding advanced English programs and activities to Padlet, will help them to improve the learning process of English writing.Keywords: Padlet, Students’ Perception, English Writing.